MARAI – Maturity Assessment Readiness Index for AI in Insurance - Jayaprakash, Prasanna Venkatesh (Digital Repository of Theses - SSBM Geneva, 2024)
The Insurance industry, one of the oldest sectors globally, has always been at the forefront of adopting new technologies to enhance its operations and services. This industry, encompassing life, property, and casualty insurance, operates through various departments such as actuarial management, customer and broker management, and both front and back-office operations. Recently, there has been a significant shift towards integrating Artificial Intelligence (AI) into these operations, driven by the broader trend of digital transformation in business processes. Gartner, in its analysis of strategic technology trends, highlighted AI engineering as a pivotal development (Panetta, 2021). AI's disruptive potential is evident in its advancements in vision, speech, and text processing, attracting substantial investments from tech giants like Google, Microsoft, IBM, Amazon, and Facebook. The insurance industry, in its quest for innovation and efficiency, has leveraged AI to reimagine traditional business models and operational strategies. Despite these advancements, there lacks a benchmark or standard index to gauge the maturity of AI implementation within insurance companies. This research focuses on the utilization of AI within the insurance sector, examining its impact on operational processes, identify gap faced by the industry when it comes to implementing AI in various departments within Insurance companies. The insurance sector, traditionally reliant on extensive data and complex processes, has seen AI catalyze significant changes. Technologies such as machine learning, natural language processing, and predictive analytics have introduced new efficiencies in underwriting, claims processing, and customer service, thereby enhancing accuracy, customer engagement, and operational efficiency. As AI technology evolves, its influence on the insurance industry is expected to expand, presenting both opportunities and challenges. The research study addressed various domains critical in assessing an insurance organization's maturity in AI integration: Enterprise Management and Leadership, Governance and Strategy, Technology, and Business Process, with a focus on Operations. It will evaluate alignment in management, strategy, governance, digital capabilities, automation, data strategy, and support services, highlighting areas for improvement and suggesting pathways for leveraging AI to navigate the rapidly changing landscape of the insurance industry effectively. As an outcome of the research this thesis proposes MARAI Framework (Maturity assessment readiness Index for AI in Insurance) with the focus on enabling Insurance companies to access their current state of the AI maturity in their operation and proposes areas to focus on based on their strategic implementation timeline. The same can be used by the insurance companies to address AI solution implementation across their value chain.